Presence of Atrazine in the Biological Samples of Cattle and Its Consequence Adversity in Human Health - M Javanbakht; SJ Shahtaheri; S Safi; SZ Peighambarzadeh; A Rahimi Forushani; SJ Shahtaheri; M Javanbakht; A Rahimi Forushani (Tehran University of Medical Sciences, 2011)
Background: Cattle can be considered as an important source for herbicides through nutrition. Therefore, herbicide residue in animal products is a potential human exposure to herbicides causing public health problems in human life. Triazines are a group of herbicides primarily used to control broadleaf weeds in corn and other feed ingredients and are considered as possible human carcinogens. To evaluate trace residue of these pollutants molecular imprinted solid phase extraction (MISPE) method has been developed, using biological samples.Methods: Blood samples were taken from the jugular vein of 45 Holstein cows in 3 commercial dairy farms in Khuzestan Province, Iran. Urine samples were also taken from the cows.Results: The mean ± SD concentrations of atrazine in serum and urine samples of the study group (0.739 ± 0.567 ppm and 1.389 ± 0.633 ppm, respectively) were higher (P < 0.05) than the concentrations in serum and urine samples of the control group (0.002 ± 0.005 ppm and 0.012 ± 0.026 ppm, respectively).Conclusion: Atrazine in the feed ingredients ingested by cattle could be transferred into the biological samples and consequently can be considered as a potential hazard for the public health.